2001
DOI: 10.1359/jbmr.2001.16.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Ranelate Increases Cartilage Matrix Formation

Abstract: Based on previous studies showing that strontium ranelate (S12911) modulates bone loss in osteoporosis, it could be hypothesized that this drug also is effective on cartilage degradation in osteoarthritis (OA). This was investigated in vitro on normal and OA human chondrocytes treated or not treated with interleukin-1␤ (IL-1␤). This model mimics, in vitro, the imbalance between chondroformation and chondroresorption processes observed in vivo in OA cartilage. Chondrocytes were isolated from cartilage by enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 33 publications
8
52
1
11
Order By: Relevance
“…In vitro studies revealed that SrRan has an anabolic and antiresorptive activity, which increase both the collagen and non-collagen protein synthesis [4,5], enhance pre-osteoblast differentiation [6,7], inhibit osteoclast differentiation, and function [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies revealed that SrRan has an anabolic and antiresorptive activity, which increase both the collagen and non-collagen protein synthesis [4,5], enhance pre-osteoblast differentiation [6,7], inhibit osteoclast differentiation, and function [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…П р о г р е с с в р е в м а т о л о г и и в X X I в е к е представили данные лабораторного исследования, в кото-ром СР усиливал формирование хрящевого матрикса [50]. При этом было отмечено увеличение синтеза высокомоле-кулярных протеогликанов как в нормальном суставном хряще (р<0,001), так и при ОА (р=0,02).…”
Section: таблицаunclassified
“…These findings suggest that strontium ranelate stimulates human cartilage matrix formation in vitro without activating the chondroresorption process. (Henrotin et al, 2001) …”
Section: Effects On Other Tissuesmentioning
confidence: 99%